Preserved Mucosal-Associated Invariant T-Cell Numbers and Function in Idiopathic CD4 Lymphocytopenia. (24th December 2020) - Sortino, Ornella; Dias, Joana; Anderson, Megan; Laidlaw, Elizabeth; Leeansyah, Edwin; Lisco, Andrea; Sheikh, Virginia; Sandberg, Johan K; Sereti, Irini
Abstract: Background: Mucosal-associated invariant T (MAIT) cells constitute a subset of unconventional, MR1-restricted T cells involved in antimicrobial responses as well as inflammatory, allergic, and autoimmune diseases. Chronic infection and inflammatory disorders as well as immunodeficiencies are often associated with decline and/or dysfunction of MAIT cells. Methods: We investigated the MAIT cells in patients with idiopathic CD4 + lymphocytopenia (ICL), a syndrome characterized by consistently low CD4 T-cell counts (<300 cell/µL) in the absence of HIV infection or other known immunodeficiency, and by susceptibility to certain opportunistic infections. Results: The numbers, phenotype, and function of MAIT cells in peripheral blood were preserved in ICL patients compared to healthy controls. Administration of interleukin-7 (IL-7) to ICL patients expanded the CD8 + MAIT-cell subset, with maintained responsiveness and effector functions after IL-7 treatment. Conclusions: ICL patients maintain normal levels and function of MAIT cells, preserving some antibacterial responses despite the deficiency in CD4 + T cells. Clinical Trials Registration: NCT00867269. Abstract : The number, phenotype, and function of MAIT cells in peripheral blood are preserved in ICL patients compared to healthy controls. IL-7 administration expanded the CD8 + MAIT-cell subset in ICL, with maintained responsiveness and effector functions.